Intraarticular Injection of a Cross-Linked Sodium Hyaluronate Combined with Triamcinolone Hexacetonide (Cingal) to Provide Symptomatic Relief of Osteoarthritis of the Knee: A Randomized, Double-Blind, Placebo-Controlled Multicenter Clinical Trial - Hangody, Laszlo; Szody, Robert; Lukasik, Piotr; Zgadzaj, Wojciech; Lénárt, Endre; Dokoupilova, Eva; Bichovsk, Daniela; Berta, Agnes; Vasarhelyi, Gabor; Ficzere, Andrea; Hangody, György; Stevens, Gary; et al. (Cartilage, 2018)
Objective: To evaluate the efficacy and safety of an intraarticular injection of Cingal (Anika Therapeutics, Inc., Bedford, MA) compared with Monovisc (Anika Therapeutics, Inc., Bedford, MA) or saline for the treatment of knee osteoarthritis. Design: This multicenter, double-blind, saline-controlled clinical trial randomized subjects with knee osteoarthritis (Kellgren-Lawrence grades I-III) to a single injection of Cingal (4 mL, 88 mg hyaluronic acid [HA] plus 18 mg triamcinolone hexacetonide [TH]), Monovisc (4 mL, 88 mg HA), or saline (4 mL, 0.9%). The primary efficacy outcome was change in WOMAC (Western Ontario and McMaster Universities Arthritis Index) Pain Score through 12 weeks with Cingal versus saline. Secondary outcomes included Patient and Evaluator Global Assessments, OMERACT-OARSI Responder index, and WOMAC Total, Stiffness, and Physical Function scores through 26 weeks. Results: A total of 368 patients were treated (Cingal, n = 149; Monovisc, n = 150; saline, n = 69). Cingal improvement from baseline was significantly greater than saline through 12 weeks (P = 0.0099) and 26 weeks (P = 0.0072). WOMAC Pain was reduced by 70% at 12 weeks and by 72% at 26 weeks with Cingal. Significant improvements were found in most secondary endpoints for pain and function at most time points through 26 weeks. At 1 and 3 weeks, Cingal was significantly better than Monovisc for most endpoints; Cingal and Monovisc were similar from 6 weeks through 26 weeks. A low incidence of related adverse events was reported. Conclusions: Cingal provides immediate and long-term relief of osteoarthritis-related pain, stiffness, and function, significant through 26 weeks compared to saline. Cingal had similar immediate advantages compared with HA alone, while showing benefit comparable to HA at 6 weeks and beyond.